PERSEPSI SISWA TERHADAP PENYELENGGARAAN PENDIDIKAN AGAMA ISLAM PADA SEKOLAH MENENGAH ATAS (SMA) - Soemanto Soemanto (Badan Litbang dan Diklat Kementerian Agama RI, 2007)
AbstractThe objective of the research is to describe student’s perception (Y),about: material or curriculum (X1), teacher’s model (X2), method (X3), evaluation (X4), environment (X5), tool and equipment (X6), also find out the relationship all variable with student’s perception. The research was conducted at senior high schools in: (1) Jakarta, (2) Bandung, (3) Yogyakarta, (4) Surabaya, (5) Palembang and, (6) Palangkaraya, in the first term of the 2004/2005 school years. Sample was taken by simple random sampling. The research revealed that there were positive correlation between material or curriculum (X1) and student’s perception (Y), with correlation determination 0.131, and there was positive correlation between teacher’s model (X2) and student’s perception (Y), with correlation determination 0.275. Positive correlation between method (X3) and student’s perception (Y), with correlation determination 0.233. Positive correlation between evaluation evaluation (X4) and student’s perception (Y), with correlation determination 0.252. positive corelation between environment (X5), and student’s perception (Y), with correlation determination 0.162. Positive correlation between tool and equipment (X6), ) and student’s perception (Y), with correlation determination 0.229. . Positive correlation between tool and equipment (X6), ) and student’s perception (Y), with correlation determination 0.229.